2009
DOI: 10.1038/jcbfm.2009.4
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective Role of Mitochondrial Uncoupling Protein 2 in Cerebral Stroke

Abstract: The uncoupling proteins (UCPs) are mitochondrial transporter proteins involved in proton conductance across inner mitochondrial membrane (IMM). UCP2, which is one of the members of this class of proteins, has a wide but restricted tissue distribution including brain. Its physiologic role according to emerging evidences, although still not clear, indicate that distribution of UCP2 may be related to regulation of mitochondria membrane potential (DWm), production of reactive oxygen species (ROS), preservation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
49
0
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(52 citation statements)
references
References 116 publications
(165 reference statements)
0
49
0
3
Order By: Relevance
“…As was noted above, the physiological role of UCP2 remains not quite clear, but experimental fi ndings indicate its involvement in the regulation of the mitochondrial membrane potential, production of active oxygen species, stabilization of calcium homeostasis, modulation of neuronal activity, and eventually reduction of cell injury [9]. It was found, for example, that higher expression of UCP2 correlated with neuronal survival after stroke and injury [10,11]. Increase of UCP2 expression in the brain under the effect of KA was observed by other authors [5].…”
Section: Resultsmentioning
confidence: 93%
“…As was noted above, the physiological role of UCP2 remains not quite clear, but experimental fi ndings indicate its involvement in the regulation of the mitochondrial membrane potential, production of active oxygen species, stabilization of calcium homeostasis, modulation of neuronal activity, and eventually reduction of cell injury [9]. It was found, for example, that higher expression of UCP2 correlated with neuronal survival after stroke and injury [10,11]. Increase of UCP2 expression in the brain under the effect of KA was observed by other authors [5].…”
Section: Resultsmentioning
confidence: 93%
“…Both VDAC and complex IV are regarded as classic mitochondrial markers, suggesting that AMI treatment has provided considerable mitochondrial support in these mice. PGC-1␣ plays a critical role in regulating mitochondrial biogenesis and functionality (74), whereas UCP2 is known for its role in maintaining the mitochondrial membrane potential and preventing insults from free radicals (75). Further evidence has shown that UCP2 is capable of eliciting neuroprotective effects in neurodegenerative diseases (76) and traumatic central nervous system events such as stroke (77).…”
Section: Discussionmentioning
confidence: 99%
“…UCP2 is expressed in a wide variety of tissues, including the brain (Richard et al, 1998;Richard et al, 2001). Here, UCP2 prevents neuronal death and diminishes brain dysfunction after stroke and brain trauma (Mattiasson et al, 2003;Mehta and Li, 2009). The ucp2 gene has been identified as a susceptibility gene in multiple sclerosis (MS) (Vogler et al, 2005).…”
Section: Introductionmentioning
confidence: 99%